Consumer Preferences for Rice Purchase Decisions in the City of Surabaya - Afidah, Aftah; Uchyani, Rhina; Riptanti, Erlyna Wida (Ridwan Institute, 2025)
This study aims to determine the level of consumer satisfaction with rice attributes and consumer preferences in rice purchase decisions in the city of Surabaya. The location of the study was taken based on the highest rice consumption in East Java Province, namely the city of Surabaya. Sampling was done using the non-probability sampling method. The sampling technique uses an accidental convenience sampling technique based on the spontaneity factor. Data were collected from respondents based on surveys and in-depth interviews using questionnaires. The data analysis method uses Important Performance Analysis (IPA) and Customers Satisfaction Index (CSI). The results of the study showed an Important Performance Analysis (IPA) on each rice attribute. The durability attribute occupies the first position when viewed from the average level of importance and performance, both of which are the highest positions, namely with a value of 4.55 and 4.31. Physical traits occupy the second position from the average level of importance but the performance is still lacking with a value of 4.48. Kepulenan occupies the second position from the average performance level with a score of 4.11, but the level of importance is still lacking. Meanwhile, advertising is in the lowest position when viewed from the average level of importance and performance, both in the lowest position, namely with values of 2.46 and 2.96. Based on the results of the Customer Satisfaction Index (CSI) analysis, it shows that overall consumers are satisfied with rice products with a satisfaction rate of 76.23%.